Terminological concept modelling and conceptual data modelling. (11th November 2009) - Madsen, Bodil Nistrup; Thomsen, Hanne Erdman
Ontologies are useful for many purposes. The use of an ontology is, for example, crucial for writing consistent definitions of concepts within a specific domain. In this paper, we will argue that the principles of rigorous terminology work are useful for building consistent ontologies. In many cases, developers of IT systems encounter severe problems, because they neglect the necessity of developing a proper ontology (concept model) before they develop a conceptual data model as a basis for an IT system. In this paper, we will argue that the development of an ontology is crucial for setting up a conceptual data model, and therefore it should always be added as an initial stage to data modelling. Also we will give some examples of the mapping between ontologies and conceptual data models. Future research will reveal to what extent it will be possible to set up rules for automatic mapping of concepts of an ontology into classes and attributes of a conceptual data model.